2012
DOI: 10.1590/s0034-737x2012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Teste de condutividade elétrica para avaliação do potencial fisiológico de sementes de canola

Abstract: Electrical conductivity test for the evaluation of physiological potential of seed lots of canolaThis work aimed to determinate the best water volume and immersion period used on electrical conductivity test for the evaluation of physiological potential of seed lots of canola. Four seed lots of canola were evaluated, which were firstly characterized with respect to quality through tests of germination, first germination count, seedling length and emergence on sand. The electrical conductivity test was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 8 publications
1
17
0
5
Order By: Relevance
“…However, Cruz et al (2013) did not obtain satisfactory results for recommendation of a methodology for the electrical conductivity test in this same species. In other oilseed species, such as canola (Milani, Menezes;Lopes, 2012) and sesame seed (Torres et al, 2009), a reduction in time for assessment of the electrical conductivity test was also recommended.…”
Section: Lotmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Cruz et al (2013) did not obtain satisfactory results for recommendation of a methodology for the electrical conductivity test in this same species. In other oilseed species, such as canola (Milani, Menezes;Lopes, 2012) and sesame seed (Torres et al, 2009), a reduction in time for assessment of the electrical conductivity test was also recommended.…”
Section: Lotmentioning
confidence: 99%
“…In seeds of canola, a Brassicacea oilseed crop, Milani, Menezes and Lopes (2012) observed that the electrical conductivity test distinguished seed lots in regard to vigor after 8 hours. A similar recommendation is made by Torres et al (2009) for sesame seeds.…”
Section: Introductionmentioning
confidence: 99%
“…seeds and two water volumes (25 and 50 mL), found that the release was considerably higher, regardless of the amount of seeds, when the seeds were soaked in a smaller volume of water. According to Milani et al (2012), the lower dilution of leachates (50 seeds in 25 mL) differentiates the quality of the batches in a shorter immersion time than the higher dilution (50 seeds in 50 mL).…”
Section: In B Napusmentioning
confidence: 99%
“…Similarly, Albuquerque et al (2001) determined the separate effect of the imbibition temperature in Helianthus annuus L. seeds. However, Milani et al (2012) observed a significant triple interaction (p < 0.05) when assessing the methodology of the electrical conductivity test (four batches; two volumes of water, 25 and 50 mL; and five immersion periods, 2, 4, 8, 16, and 24 h) using Brassica napus L. var. oleifera seeds, indicating that the seed batches behaved differently in each combination of water volume and immersion period.…”
mentioning
confidence: 94%
“…Pesquisas realizadas envolvendo esses testes (Silva et al, 2008;Carvalho et al, 2009) mostraram que ambos são satisfatórios na avaliação do potencial fisiológico de sementes de soja . O teste de condutividade elétrica baseia-se no fato de que o vigor está diretamente relacionado com a integridade do sistema de membranas celulares (Milani et al, 2012).…”
Section: Introductionunclassified